Comparative Proteomics Analysis Reveals the Reversal Effect of Cryptotanshinone on Gefitinib-Resistant Cells in Epidermal Growth Factor Receptor-Mutant Lung Cancer - Cai, Peiheng; Sheng, Gaofan; Jiang, Shiqin; Wang, Daifei; Zhao, Zhongxiang; Huang, Min; Jin, Jing (Frontiers in Pharmacology, 2022)
Cryptotanshinone (CTS) is a lipophilic constituent of Salvia miltiorrhiza, with a broad-spectrum anticancer activity. We have observed that CTS enhances the efficacy of gefitinib in human lung cancer H1975 cells, yet little is known about its molecular mechanism. To explore how CTS enhances H1975 cell sensitivity to gefitinib, we figured out differential proteins of H1975 cells treated by gefitinib alone or in combination with CTS using label-free liquid chromatography-tandem mass spectrometry (LC-MS/MS). Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and protein–protein interaction (PPI) bioinformatic analyses of the differential proteins were performed. CTS enhanced H1975 cell sensitivity to gefitinib in vitro and in vivo, with 115 and 128 differential proteins identified, respectively. GO enrichment, KEGG analysis, and PPI network comprehensively demonstrated that CTS mainly impacted the redox process and fatty acid metabolism in H1975 cells. Moreover, three differential proteins, namely, catalase (CAT), heme oxygenase 1 (HMOX1), and stearoyl-CoA desaturase (SCD) were validated by RT-qPCR and Western blot. In conclusion, we used a proteomic method to study the mechanism of CTS enhancing gefitinib sensitivity in H1975 cells. Our finding reveals the potential protein targets of CTS in overcoming gefitinib resistance, which may be therapeutical targets in lung cancer.